Estratégias de síntese de catalisadores à base de ferro e molibdênio utilizando elementos metálicos - Mesquita, Aline Marques (2018)
The study was carried out with the objective of developing catalysts based on iron and molybdenum by means of new synthesis strategies. The syntheses were carried out using the modified polymer precursor method, the main changes were the use of metal precursors and ammoniacal oxalate of niobium as a complexing/oxidizing agent. In this way, two series of materials were produced; the first using ammonium niobium oxalate and the second using citric acid with different Fe / Mo ratios (mol/mol %): 100:0; 99.5:0.5; 99:1; 97.5:2.5; 95:5; 90:10; 80:20; and 70:30. In a first step of the process, the metallic elements of iron and molybdenum were oxidized and as a final stage of the method, in order to obtain the particles, the co-precipitation of the produced oligomers was carried out. The formation of the materials was confirmed by SEM/EDS, FTIR, XRD, H-RTP, and XPS analyzes. The association of these techniques showed that the metal atoms were oxidized to Fe2+ and/or Fe3+, Mo6+ and Mo4+. In addition, these elements interact without a segregated phase formation. When tested for methylene blue discoloration, these materials showed high color removal ability of the compound, with the best rates for the materials with 20 and 30% of molybdenum.